IN SILICO ANALYSIS PREDICTS AN AMINO ACID PERMEASE FAMILY PROTEIN AS THE PUTATIVE CANDIDATE GENE UNDERLYING A MAJOR QTL FOR TILLER NUMBER IN RICE (Oryza sativa L.) - KEERTHI ISSA, LAKSHMINARAYANA R. VEMIREDDY, ESWARAYYA RAMI REDDY, LAL AHAMED MOHAMMAD; P. LAVANYA KUMARI (The Journal of Research ANGRAU, 2022)
Rice (Oryza sativa L.) yield and it’s component traits are known to have complex inheritance and are controlled by several genes with small effects. Although several genomic regions or quantitative trait loci (QTLs) are identified for a galaxy of traits in rice, only a few candidate genes underlying these QTLs have been functionally characterized as involvement of the laborious and time-consuming fine mapping and map-based cloning strategies. However, with the advances in sequencing technologies, now a wealth of information related to genomics, transcriptomics, proteomics and metabolomics has been publicly available. Exploiting these databases, in the present investigation, we predicted amino acid permease (AAP) (LOC_Os01g71720), as a candidate gene underlying a major effective QTL for tiller number. The candidature of the OsAAP for tiller number QTL has been endorsed by the literature mining, QTG finder, GO analysis, sequence variation, and gene expression analysis. Therefore, this OsAAP could be targeted for further functional analysis before being exploited in future rice breeding.